Plein soleil = Purple noon [videorecording (DVD)] - Clément, René, 1913-1996; Clément, René, 1913-1996; Delon, Alain, 1935-; Laforêt, Marie; Ronet, Maurice, 1927-1983; Crisa, Erno, 1924-1968; Latimore, Frank, 1925-1998; Kearns, Billy; Ninchi, Ave, 1914-1997; Chantel, Viviane; Bernardi, Nerio, 1899-1971; Highsmith, Patricia, 1921-1995 (Criterion collection (DVD videodiscs) ;, 2012)
An adaptation of Patricia Highsmith's novel The Talented Mr. Ripley, this film stars Alain Delon as Tom Ripley, a duplicitous American charmer in Rome on a mission to bring his privileged acquaintance Philippe Greenleaf back to the United States; what initially seems a carefree tale of friendship soon morphs into a thrilling saga of seduction, identity theft, and murder.